Decidim, a Technopolitical Network for Participatory Democracy Philosophy, Practice and Autonomy of a Collective Platform in the Age of Digital Intelligence - Barandiaran, Xabier E.; Calleja-López, Antonio; Monterde, Arnau; Romero, Carol (SpringerBriefs in Political Science, 2024)
This Open Access book explains the philosophy, design principles, and community organization of Decidim and provides essential insights into how the platform works. Decidim is the world leading digital infrastructure for participatory democracy, built entirely and collaboratively as free software, and used by more than 500 institutions with over three million users worldwide. The platform allows any organization (government, association, university, NGO, neighbourhood, or cooperative) to support multitudinous processes of participatory democracy. In a context dominated by corporate-owned digital platforms, in the era of increasing social structuring via Artificial Intelligence, Decidim stands as a public or community owned platform for collective human intelligence. Yet, the project is much more than its technological features. Decidim is in itself a crossroad of the various dimensions of the networked society, a detailed practical map of its complexities and conflicts. Theauthors distinguish three general dimensions of the project: (1) the political - shedding light on the democratic model that Decidim promotes and its impact on public policies and organizations, (2) the technopolitical - explaining how this technology is democratically designed and managed to produce and protect certain political effects, and (3) the technical - presenting the conditions of production, operation, and success of the project. This book systematically covers those three levels in an academically sound, technologically consistent, and politically innovative manner. Serving as a useful resource and handbook for the use of Decidim, it will not only appeal to students and scholars interested in participatory and digital democracy but also to professionals, policy-makers, and a wider audience interested in learning more about the Decidim platform. This is an open access book.